2017
DOI: 10.1016/j.celrep.2017.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Mass Cytometry and Topological Data Analysis Reveal Immune Parameters Associated with Complications after Allogeneic Stem Cell Transplantation

Abstract: Highlights d Mass cytometry data analysis after allogeneic stem cell transplantation d Perturbed co-regulation patterns of cells and proteins are associated with complications d Topological data analyses allow for the integration of cell, protein, and metadata d Cytomegalovirus has a profound impact on the regenerating immune system

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…A study using the same analysis method as the present study, but with patients undergoing allogeneic HSCT for acute leukemia and/or myelodysplastic syndrome noted a transient burst, decay, or slow increase or decrease in several of the proteins at 3 months after the procedure [36]. The authors suggested that the overrepresentation of proteins involved in cell proliferation, IL-2 signaling, and allograft rejection among the "3-month burst" proteins implied that these processes are particularly active during this phase of immune regeneration.…”
Section: Discussionmentioning
confidence: 55%
“…A study using the same analysis method as the present study, but with patients undergoing allogeneic HSCT for acute leukemia and/or myelodysplastic syndrome noted a transient burst, decay, or slow increase or decrease in several of the proteins at 3 months after the procedure [36]. The authors suggested that the overrepresentation of proteins involved in cell proliferation, IL-2 signaling, and allograft rejection among the "3-month burst" proteins implied that these processes are particularly active during this phase of immune regeneration.…”
Section: Discussionmentioning
confidence: 55%
“…Most notably, none of the 15 publications explicitly stated that the provided data underwent randomization. To the best of our knowledge, the only non‐randomized public data set has been announced in , during the preparations of this article.…”
Section: Resultsmentioning
confidence: 99%
“…Other approaches dedicated to identifying differential immune cell frequencies in groups of samples can be applied, including approaches relying on statistical comparisons of cluster frequencies (Bruggner et al, 2014;Spitzer et al, 2017), convolutional neutral networks (Arvaniti and Claassen, 2017), empirical Bayes moderated tests (Weber et al, 2018) or hyperspheres (Lun et al, 2017). Since these approaches typically require advanced computational skills, we additionally demonstrate compatibility of this experimental workflow with a fully-automated, commercial analysis platform (astrolabediagnostics.com) to perform a systems-level analysis of immune cell reconstitution following BMT (Lakshmikanth et al, 2017;Stern et al, 2018) and to identify factors associated with the development of acute GvHD (Stikvoort et al, 2017). Albeit preliminary due to the limited sample number and potential confounding factors, we demonstrated the utility of our framework to identify such diseaseassociated cellular immune signatures in a clinical cohort.…”
Section: Discussionmentioning
confidence: 99%